A QUALITATIVE ANALYSIS: SERVICE QUALITY AND CUSTOMER SATISFACTION OF BNI SELF-SERVICE OPENING ACCOUNT (BNI SONIC) - Rambing, Maria; Mangantar, Maryam; Gunawan, Emilia (Universitas Sam Ratulangi, 2022)
Service quality is the process when the service has already delivered to the consumer and also generally refers to a customer's comparison of service expectations. Customer satisfaction and service quality is inter-related. Service quality and customer satisfaction are widely recognized as key influences in the formation of consumers' purchase intentions in service environments. Service quality means a form of an attitude, related but not equivalent to satisfaction that results from the comparison of expectation with performance. To achieve these objectives the researcher got information from 15 informants using qualitative study which is in-depth interview and uses purposive sampling. In order to get the best result, researcher took the entire informants that have been visit and open BNI Account at BNI Banking Cafe. The results showed that Service Quality is important to the Self Service Technology of BNI SONIC. All the respondents said that the performance, reliability and responsiveness of self-service BNI SONIC is good and they are very happy with the existence of Self Service BNI SONIC. The service quality includes the performance of Self Service BNI SONIC. Keywords: service quality, customer satisfaction